Energetics of ion permeation in an open-activated TRPV1 channel. - Jorgensen, C; Furini, S; Domene, C (Elsevier, 2016)
Ion channels enable diffusion of ions down physiological electrochemical gradients. Modulation of ion permeation is crucial for the physiological functioning of cells, and misregulation of ion channels is linked to a myriad of channelopathies. The ion permeation mechanism in the transient receptor potential (TRP) ion channel family is currently not understood at an atomistic level. In this work, we employed a simulation strategy for ion permeation (molecular-dynamics simulations with bias-exchange metadynamics) to study and compare monovalent (Na(+), K(+)) ion permeation in the open-activated TRP vanniloid-1 (TRPV1) ion channel. Using ∼3.6 μs of simulation trajectories, we obtained atomistic evidence for the nonselective nature of TRPV1. Our analysis shows that solvated monovalent ions permeate through the selectivity filter with comparable energetic barriers via a two-site mechanism. Finally, we confirmed that an intracellular binding site is located between the intracellular gate residues I679 and E684.